Confırmatory Factor Analysıs Of Fısherman Sustaınabılıty Indıcators In Bıreuen Dıstrıct - adhiana Adhiana; Martina Martina; Riani Riani; Ade Firmansyah Tanjung; Madeline Berma (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Bireuen Regency is one of the districts that has great potential in the field of fisheries. Most fishermen still live in limitations and poverty, and this situation can be seen from the level of their survival which can be measured from the economic, social, natural environment and reduced vulnerability. This study aims to identify economic, social, environmental aspects and reduce vulnerability to the survival of fishermen in Bireuen Regency using the Confirmatory Factor Analysis (CFA) method. This research location was conducted in Bireuen Regency, namely in Peudada and Jangka Districts. The selection of these two sub-districts was carried out by purposive sampling because these sub-districts are the largest capture fisheries production centers in Bireuen Regency. The population is all fishermen in the two sub-districts. The number of samples was 124 fishermen using the Accidental Sampling technique method. Based on the analysis it was found that the most dominant latent variable for survival can be seen from the economic aspect is the increase in the sale of catches, the social aspect is the participation of fishermen in knowledge-building activities, the surrounding natural aspect is planting mangrove trees around the beach, and the reduced vulnerability aspect is the availability of opportunities